(untitled) (Revista Educação, Artes e Inclusão, 2022)
This article discusses guidelines for the construction of a cultural mediation methodology for basic education, taking as reference the results obtained in the classroom application of two educational materials focused on contemporary art: Sensation and Materiality: the work, its visual and sensory composition and Educational Curatorship for Videodance. Both were produced and tested within the scope of theteaching, research and extension Project Mediation of aesthetic experience at school, at the University of Minas Gerais State - UEMG. Based on a series of conceptual and methodological premises, the Project seeks to integrate aesthetic and ethical education, relying on the ideas of John Dewey, Michael Parsons, Teresinha Franz and George Geahigan, among other scholars. The two educational materials were applied in two public schools of Belo Horizonte between August and October 2017, involving two mediators of the project team, two teachers and six classes of elementar school, reaching approximately 150 students. At the end of the process, all participants evaluated the materials using instruments developed specifically for this purpose. The article relates the results achieved with the theoretical references of the project, seeking to identify guiding principles for cultural mediation in the teaching of visual arts.